A descriptive analysis on the personality of child physical abuse victims - Mansor, Mariani; Abu Samah, Asnarulkhadi (Center for Promoting Ideas, 2011)
This paper discusses on the personality development of physically abused children from region in Malaysia. A total of 106 children from five protection homes and shelters were as respondents for this study. A quantitative and qualitative methods were employed to appraise respondent’s personality, using a personality questionnaire and a projective human figure drawing techniques. Respondents’ personality development was measured based on their personal and social adjustment subscales. Analysis on the personality subscales showed that the overall level for respondents’ personality adjustment was rather low, with mean of 71.3% and 70.8% simultaneously. Similarly, qualitative analysis on respondents’ drawings also indicated problems in their personality development, with majority of them showed anxiety (84.2%), impulsive (73.3%), aggression (65.3%) and insecurity (55.5%) characteristics. The study demonstrated that experience of abusive treatment leave an impact on victims personality development, specifically on their emotional adjustment, which may further influence their future wellbeing.